2002
DOI: 10.1055/s-2002-26707
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Modulation of Circulating Leptin Levels: Site-Specific Changes in Fat Deposition and Ob mRNA Expression

Abstract: In order to study the effects of diet on fat distribution, circulating leptin levels and ob mRNA expression, diets of different macronutrient composition were fed to lean mice and gold thioglucose-obese mice. A high-fat diet and 2 high-carbohydrate diets, one containing mostly high-glycaemic-index starch and the other containing low-glycaemic-index starch were fed ad libitum for 10 weeks and were compared to standard laboratory chow. Weight gain was attenuated by feeding low-glycaemic-index starch in all mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 33 publications
(48 reference statements)
3
23
0
Order By: Relevance
“…30,31 The amount of leptin mRNA was reduced in fasted rats prior to the glucose challenge, as previously reported. 4,5,30,32 This decreased amount of leptin mRNA in EWAT of fasted rats may reduce the capacity for de novo leptin synthesis compared to the EWAT of fed rats.…”
Section: Discussionsupporting
confidence: 76%
“…30,31 The amount of leptin mRNA was reduced in fasted rats prior to the glucose challenge, as previously reported. 4,5,30,32 This decreased amount of leptin mRNA in EWAT of fasted rats may reduce the capacity for de novo leptin synthesis compared to the EWAT of fed rats.…”
Section: Discussionsupporting
confidence: 76%
“…Animal studies show a more consistent effect of dietary GI on the leptin response and support the idea that dietary macronutrient content as well as dietary GI contribute to variations in circulating plasma leptin levels [39,40] . Animal studies uniformly observe that following a high glycemic diet both plasma leptin and leptin mRNA expression in fat are significantly decreased [39,40] .…”
Section: Discussionsupporting
confidence: 63%
“…Animal studies uniformly observe that following a high glycemic diet both plasma leptin and leptin mRNA expression in fat are significantly decreased [39,40] . Recently, Pawlak et al [41] demonstrated the independent and adverse effects of dietary glycemic index on body composition and risk factors for diabetes and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of high-vs. low-GI diets on molecular markers of fat metabolism have been investigated only in a few previous studies (12,23,24). After long-term high-vs. low-GI exposure, the expression of important enzymes in regulation of de novo lipogenesis such as Acc and Fas was significantly elevated.…”
Section: Discussionmentioning
confidence: 99%